FISCAL EQUALIZATION AND REGIONAL GROWTH - Capkova, Sona; Roncakova, Lucia (European Scientific Journal, ESJ, 2014)
The year 2013 is already the ninth year of implementing fiscal decentralization in the Slovak Republic. The aim was to ensure independence as well as responsibility of subnational governments and improve the ability to finance their original competences from own sources. As decentralization leads to growth of imbalance intergovernmental transfers are the instruments used by central government to reduce fiscal disparities and fill the gap between the spending needs and fiscal capacity of some local authorities. Tax sharing system in Slovakia, is an important tool of horizontal fiscal imbalance equalisation. Despite the title, shared taxes play the role of unconditional grants if even they are formally labelled as local government own revenues under current legislation. In this paper we examine the allocation of personal income tax share as an instrument of regional policy and factors affecting interregional disparities in Slovakia. The paper presents some results of the research project VEGA1/0822/11 Redistribution of financial resources in the decentralized fiscal system in Slovakia.